Analisis Dampak Lalu Lintas bagi Perumahan Sebagai Upaya Mengatasi Kepadatan Lalu Lintas Kabupaten Sleman - Isviati Joenaini Koenti; Author Risdiyanto (Fakultas Hukum Universitas Islam Indonesia, 2015)
The first and foremost issue in this study is how is the licensing regulations of housing and transportation policies in the city? Second is how is the relationship between generation and attraction of Sidoarum Housing crossing Godean street? Third is how the prospect of housing permits settings integrated with the analysis of the impact of traffic? This is an empirically normative research. It leads to a conclusion that first, the laws and regulations related to housing both in the provincial and district levels are still partial, sectoral, and not synchronized with the plan of spatial and territories. So far there is no regulation which relates housing with traffic density at the local level. Second, the level of housing density in Godean street and the current traffic density has increased from year to year thronging the open roads connecting Godean (as the densely populated residential areas) towards the city as an economic, offices, and educational center and causing high degree of saturation, comprising of 7749 and 9141 generation of traction. Thus, the density of housing in an area highly affects traffic density. Third, it is recommended that housing licensing regulations be regulated in an integrated manner with the housing permit obligations of Traffic Impact Analysis (Andalalin) for housing with certain capacity in a regional regulation.